THE APPLICATION OF THE DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS' LEARNING OUTCOMES IN ELASTICITY AND HOOKE LAW MATERIALS IN CLASS XI IPA 1 SMA NEGERI 1 PURI - Suprapti (Sean Institute, 2022)
Ideally, the learning process should be carried out by fully involving the activities of students, but what happens is that learning is more dominated by educators so that student learning outcomes are limited. This research is a type of Classroom Action Research (CAR) using the Kemmis and Taggart models which was carried out in two cycles with two meetings per cycle, each cycle consisting of planning, implementation, observation and reflection stages. The subjects of this study were all 36 students of class XI IPA 1 SMA Negeri 1 Puri. Data collection methods are documentation, observation, tests, and field notes. The results show that the application of the discovery learning method can improve the quality and learning outcomes of students, this is shown from the data on the implementation of lesson plans reaching 100% in both cycles and student activities in the active category, scientific behavior in the good category, as well as positive student responses and an increase completeness of student learning outcomes in each cycle, namely cycle I (66.67%), cycle II (86.11%).